The effect of the omega-3 supplement on uremic pruritus in hemodialysis patients; a double-blind randomized controlled clinical trial - Shokouh Shayanpour; Seyed Seyfollah Beladi Mousavi; Parastoo Lakhaye Rizi; Bahman Cheraghian (Society of Diabetic Nephropathy Prevention, 2019)
Background: Chronic kidney disease (CKD) and uremic syndrome cause malfunction in most of organs including skin. Objectives: This study was designed to investigate the effects of omega-3 supplement on uremic pruritus in chronic hemodialysis patients. Patients and Methods: In this double-blind randomized controlled clinical trial study (#IRCT cod; 29363; http://irct.ir/trial/29363), the effect of the omega-3 supplement on uremic pruritus was assessed in 64 chronic hemodialysis patients (using standard 5-D itch scale questionnaire). Patients were surveyed at the hemodialysis department of Imam Khomeini and Razi hospitals in Ahvaz city, Iran. Results: We found that the mean score of itching degree in the intervention and the placebo groups decreased from 3.56 to 1.72 (P<0.001) and 3.63 to 3.09 (P<0.05) respectively. Conclusions: In our study, the omega-3 supplement could reduce uremic pruritus in chronic hemodialysis patients.